EFEKTIVITAS SISTEM E-PERFORMANCE DALAM MENUNJANG KINERJA PEGAWAI DI KECAMATAN GUNUNGANYAR KOTA SURABAYA PROVINSI JAWA TIMUR - Nangameka, Teresa Irmina; Anshori, Ahmad Ridho (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT As a journal, entitled “The effectiveness of system e-performance in supporting the performance of employees in Gununganyar Distri Surabaya City East Java Province the province of east java”, the purpose is to understand how effective and efficiency of e-performance application in supporting activities and outputs of employees that called performance by using qualitative methods and types of descriptive research where data retrieval is performed with interviews, observation and documentation. In the informant determination of research this time using purposive sampling technique and snowball, there are Head of District, Administrator of e-Performance, and Staffs on that dictrict. The researchers used a Qualitative analysis with data reduction steps, the presentation of the data, and draw conclusions. Analysis result has indicated that there are significant qualifications of e-performance systems in supporting the output and activities of employees. The conclusion that obtained from the research this time was more effectiveness from implementation of the e-performance program in Gununganyar District. The author would suggest that the government should provide assistance in the form of infrastructure, socializing on a regular basis, the rules regarding e-Performance Openness which should be increased and the need for evaluation of it. Keywords: effectiveness, e-performance, performance